2011
DOI: 10.1523/jneurosci.0418-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Study of Novel Selective mGlu2 Agonist in the Temporo-Ammonic Input to CA1 Neurons Reveals Reduced mGlu2 Receptor Expression in a Wistar Substrain with an Anxiety-Like Phenotype

Abstract: Group II metabotropic receptors (mGluRs) regulate central synaptic transmission by modulating neurotransmitter release. However, the lack of pharmacological tools differentiating between mGlu2 and mGlu3 receptors has hampered identification of the roles of these two receptor subtypes. We have used LY395756 [(1SR,2SR,4RS,5RS,6SR)-2-amino-4-methylbicyclo[3.1.0]-hexane2,6-dicarboxylic], an agonist at mGlu2 receptors and an antagonist at mGlu3 receptors in cell lines, to investigate the roles of these receptors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 54 publications
1
25
1
Order By: Relevance
“…Furthermore, we also demonstrate selective mGlu8 antagonism by (RS)-a-methyl-3,4-dicarboxyphenylglycine (MDCPG) (Thomas et al, 2001) in the LPP. In order to directly assess the non-selective effects of DCPG, we used slices from mice lacking mGlu8, mGlu2, mGlu4 or mGlu7 receptors, as well as from a rat strain lacking functional mGlu2 receptors (Ceolin et al, 2011). The present investigation has demonstrated that submicromolar concentrations of DCPG are selective for mGlu8 receptors but that higher concentrations lead to activation of mGlu2 receptors, thus complicating the interpretation of some in vivo studies.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, we also demonstrate selective mGlu8 antagonism by (RS)-a-methyl-3,4-dicarboxyphenylglycine (MDCPG) (Thomas et al, 2001) in the LPP. In order to directly assess the non-selective effects of DCPG, we used slices from mice lacking mGlu8, mGlu2, mGlu4 or mGlu7 receptors, as well as from a rat strain lacking functional mGlu2 receptors (Ceolin et al, 2011). The present investigation has demonstrated that submicromolar concentrations of DCPG are selective for mGlu8 receptors but that higher concentrations lead to activation of mGlu2 receptors, thus complicating the interpretation of some in vivo studies.…”
Section: Introductionmentioning
confidence: 95%
“…We sought to further investigate the effects of DCPG in a substrain of Wistar rat identified as lacking mGlu2 receptor expression (Ceolin et al, 2011). For these experiments, Hsd:Wi rats were ordered from Harlan (UK), and western blot analyses were performed on the remaining hippocampal slices from each animal following electrophysiological recording, in order to estimate mGlu2 receptor expression levels.…”
Section: Non-selective Dcpg Effects Are Reduced In Rats With Low Mglumentioning
confidence: 99%
“…LY395756 (LY39) is a novel compound that serves as both an mGluR2 agonist and mGluR3 antagonist (K i = 0.165 and 0.302 μM, respectively) (Ceolin et al, 2011; Lucas et al, 2013). We ewcently observed that LY39 also exhibited a strong effect on AMPAR expression in cultured neurons (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another study in mice revealed the antinociceptive effect of NPS on inflammatory pain [44]. The amygdala has been implicated in the integration of pain and mood disorders [3; 8; 12; 61]. NPS-responsive neurons express NPSR and are concentrated in the amygdala [11; 59].…”
Section: Introductionmentioning
confidence: 99%